The Effectiveness of Relaxation Intervention on Psychophysiological Responses in Patients Undergoing Cardiac Catheterization: A Systematic Review - Nora Dwi Purwanti; Tuti Herawati; Amelia Kimin (Universitas Pahlawan Tuanku Tambusai, 2026)
Coronary artery disease (CAD) is a major contributor to global mortality and leads to a high number of cardiac catheterization procedures, including coronary angiography (CAG) and percutaneous coronary intervention (PCI). These invasive procedures often trigger psychological responses such as anxiety and physical responses such as pain. Unmanaged pain may contribute to autonomic dysregulation and worsen cardiovascular outcomes. This systematic review aimed to synthesize scientific evidence on the effectiveness of relaxation interventions on the psychophysiological responses of patients undergoing cardiac catheterization. The review followed PRISMA 2020 guidelines and searched five databases: PubMed, Scopus, EBSCOhost, ProQuest, and Google Scholar. The PICOS framework was used to identify randomized controlled trials (RCTs) published between 2016 and 2026. Article quality was assessed using the Cochrane Risk of Bias tool version 2 (RoB 2). Eight RCTs were included in the analysis. Interventions identified included Benson relaxation, progressive muscle relaxation (PMR), deep breathing exercises, and music therapy. Results showed that relaxation interventions significantly reduced anxiety and pain levels. Although findings on hemodynamic parameters varied, improvements in cardiovascular regulation, heart rate variability, and cortisol levels were observed. Relaxation interventions are safe, effective, and support evidence-based nursing care practices.